An Overview on Wetland Ecosystem – Interplay of Factors Influencing Microclimate and Seasonal Variation - Mathews P. Raj; Reena Susan Philip (Cutting Edge Research in Biology Vol. 6, 2023)
Water, is one of the basic requirement for the survival of human beings, flora, and fauna. Wetlands have been used as a source of water, and also as dump grounds for discharging sewage and other human waste. Water and water bodies have been overexploited as a result of urbanization and industrialization, and they are disappearing at an exponential rate. Seasonal variations and anthropogenic activities have a significant impact on water quality, microclimate, and aquatic diversity. Researches reviewed in this study indicate that the various parameters are interdependent with each other and influence the productivity, biodiversity, and ultimately the micro-climate and seasonal variations of a wetland ecosystem. The objective of this presented review is to understand the role of dependency and interdependency of various paramenters such as physical, chemical and biological which influences the microclimate of a narrow region contributing to seasonal variations. It is well known that physical and chemical factors, such as pH, temperature, chlorophyll content, light, and phosphate content, have a direct impact on productivity and biodiversity. The microclimate and seasonal variations of a wetland are further impacted by changes in productivity and biodiversity. Additionally, modifications of chemical parameters affect modifications of physical parameters, and vice versa. Additionally, changes in productivity and biodiversity are influenced by physical and chemical factors. The interactions between different parameters that control the microclimate and seasonal variations are established by this study. This review establishes the foundation for related research on wetland ecosystems to improve sustainability and maintenance practices.